1998
DOI: 10.3141/1618-16
|View full text |Cite
|
Sign up to set email alerts
|

Usage, Impacts, and Benefits of Innovative Transit Pass Program

Abstract: An evaluation of an innovative transit program, UPASS, is summarized. UPASS provides unlimited use of the Milwaukee County Transit System at any time and any place and for any purpose for all students enrolled at the University of Wisconsin-Milwaukee. The pass program, paid for by a special fee attached to students’ tuition, was implemented in fall 1994 and was extensively evaluated to determine its impact on ridership and other factors and to determine whether the concept has the potential for transfer to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…However, we are aware that an increase in active transport use may occur as an unforeseen side effect of interventions with a different aim. For example, Lane (2005) showed that a carsharing programme in Philadelphia reduced vehicle ownership after one year and caused a mode shift from car driving to active transport and Meyer and Beimborn (1998) showed that the implementation of the UPASS (a pass which provides students with unlimited transit travel) reduced car use and increased transit use as well as walking. Future research could also include such interventions.…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 98%
“…However, we are aware that an increase in active transport use may occur as an unforeseen side effect of interventions with a different aim. For example, Lane (2005) showed that a carsharing programme in Philadelphia reduced vehicle ownership after one year and caused a mode shift from car driving to active transport and Meyer and Beimborn (1998) showed that the implementation of the UPASS (a pass which provides students with unlimited transit travel) reduced car use and increased transit use as well as walking. Future research could also include such interventions.…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 98%
“…Several case studies of U-Pass programs have shown that they increase ridership (Boyd, 2003;Brown, 2003Meyer et al, 1998Meyer et al, 2006). Fare elasticities of transit demand across campuses in the United States range from -0.26 to -0.50 (Brown, 2001), implying that free transit would increase transit demand by 26-50%.…”
Section: U-passmentioning
confidence: 99%
“…Importantly, students have free transit passes, called UPASS, to access MCTS buses during the semesters they enroll. The UPASS program was implemented in 1994, and it was successful in shifting some automobile users to commute by bus (22).…”
Section: Study Areamentioning
confidence: 99%